Using Skin‐to‐Skin Contact to Increase Exclusive Breastfeeding at a Military Medical Center. Issue 6 (December 2015) - Hughes, Kimberly N.; Rodriguez‐Carter, Jann; Hill, Jennifer; Miller, Dena; Gomez, Crystal
Abstract: Evidence shows that early formula supplementation leads to early weaning from exclusive breastfeeding. We implemented an evidence‐based practice project on skin‐to‐skin contact (SSC) for healthy term newborns at a large military treatment facility in an effort to decrease formula supplementation in the early postpartum period. Military women face unique challenges when it comes to breastfeeding. SSC in the early postpartum period is an effective intervention to increase exclusive breastfeeding during the hospital stay and foster future positive breastfeeding outcomes. Through this project, staff knowledge of the benefits of SSC to women and newborns improved and the hospital's exclusive breastfeeding rate increased by 20 percent.